Musical and Extra-Musical Texts in Christian Worship (Based on Marco Demarinis' Semantic Theory) - Tompo, Hengki; Sasongko, Michael Hari (Jurnal Apokalupsis, 2024)
Fundamentally, music as a performance exhibits two characteristics: musical and extra-musical. These two elements are interconnected, complementary, and inseparable. Musical elements cannot be fully understood without considering the surrounding aspects, which lie outside the music itself. This dual nature also applies to church music. However, music used in and for worship is also a performance. This research examines the presence of these two characteristics in musical performances during Christian worship. Through Marco DeMarinis' semiotic theory, these two characteristics are manifested in the relationship between text, co-text, and context. The study's findings demonstrate that musical elements are no more important than extra-musical elements because in Christian worship, the Word is the ultimate objective of a liturgy: Without music, Christian worship can still occur, but without the Word, worship cannot be conducted.